European Instructional Lectures Volume 9, 2009; 10th EFORT Congress, Vienna, Austria - Bentley, George (European Instructional Lectures,, 2009)
The individual lectures on orthopaedics and trauma topics collected in this book range from fractures of the cervical spine to the treatment of club foot in children. They contain essential information for trainees and the latest information on the developments in the field.